Theory, Epistemology and Critical Rural Sociology - Bonanno, Alessandro; E. Swanson, Louis (The International Journal of Sociology of Agriculture and Food, 2021)
This paper would like to provide an alternative to the Marx-Weber dichotomy which has recently emerged in rural sociological studies. It consists of the re-proposition of critical sociology as a mode of scientific investigation which, while remaining within the Marxian tradition, addresses many of the central concerns of Weberian scholarship. Though a merger between Marx and Weber is not proposed, it is assumed that a lack of knowledge of critical sociology has hampered further development of the theoretical debate in rural sociology. More importantly, this lack of knowledge has prevented the diffusion of the basic tenets of critical sociology among sociologists concerned with the study of agriculture and food, limiting their ability to inform empirical investigations and to instruct students. ResumenTeoría Crítica, Epislemología y Sociología Rural Este trabajo trata de proveer una alternativa a la dicotomia Marx-Weber que recientemente a emergido en los estudios sociológicos rurales. Consiste en una re-proposición de la sociología crítica como un modo de investigación científica que, aún permaneciendo dentro de la tradición marxista, puede dirigirse a muchos aspectos concernientes al saber Webweriano. Aunque una integración entre Marx y Weber no es propuesta, se parte del supuesto de que una falta de conocimeinto de sociología crítica tiende a estorbar el fomento y desarrollo del debate teórico en sociología rural.Mas importantemente, esta falta de conocimiento ha trabado la difusión de los fundamentos básicos de la sociología crítica entre sociólogos que se ocupan de los estudios de la agricultura y alimentos, limitando la información de la investigación empírica y la enseñanza a los estudientes.